Activity-based costing (ABC) : the testing & implementation of a contingency model - Lim, Bee Keow (2014)
With the increased use of automation in industries (especially manufacturing), overheads have formed a significant portion of total costs. Traditional cost drivers such as direct labour hours that were used to allocate overheads were no longer accurate and reliable. Cooper and Kaplan (1980) suggested the use of activities related to the production of the product as cost drivers. They propagated the virtues of the activity-based costing (ABC) system.